Local community: interpretation of the concept - Natalia Vladimirovna Demchuk (Вестник Майкопского государственного технологического университета, 2023)
The article examines and compares different approaches to understanding the essence of a local community as a complex social phenomenon combining characteristics of a social group and a social community. On the basis of methods of systematization, generalization and comparison of various theoretical approaches to understanding the essence of a local community, it has been concluded that there are two main approaches to the definition of the local community in the modern scientific literature: a communitarian and a socio-territorial. The communitarian approach considers communities as derived from the communication (interaction) of social objects. The socio-territorial approach defines local communities through the presence of a common beginning that unites people. The diversity of interpretations of the concept of “local community” emphasizes a complex nature of the studied processes. The research substantiates understanding of the local community as a special stage of development of a socio-territorial community. The local community is considered as a set of horizontal social relations (relationships) between people, generated by the interaction of a set of people living in the territory of a municipality, having common interests and values, aware of the need to combine action to solve local issues and interacting on solving local issues. Consideration of the local community as a stage in the development of a socio-territorial community will make it possible to apply new empirical methods for its study using sociological methods.